Project-based learning to develop leadership competencies in higher education students - Sousa, M.; Sousa, M. (ICERI2020 Proceedings, 2020)
This article analyses the concept of competencies and identifies the competencies needed by Higher Education Students to lead projects; to accomplish those goals the primary step was to determine the leadership competencies developed by Universities regarding project based learning processes and compare it to the competencies perceived as needed by students. The research problem is anchored to the following research questions: What were the level of leadership competencies developed in the higher education courses regarding the application of Project-Based Learning methodology?; What were the relationships between the perceived competencies development and the factors gender, and course? The leadership competencies identified by the students were pointed out through questionnaire applied to 76 students by an online survey. The primary outcome of the research will be a proposal of a model of leadership competencies development for students to potentiate their leadership capacity as project leaders.